Multimission observations of the old nova GK Per during the 2015 outburst - Zemko, P. (2017)
GK Per, a classical nova of 1901, is thought to undergo variable mass accretion on to a magnetized white dwarf (WD) in an intermediate polar system (IP). We organized a multi-mission observational campaign in the X-ray and ultraviolet (UV) energy ranges during its dwarf nova (DN) outburst in 2015 March-April. Comparing data from quiescence and near outburst, we have found that the maximum plasma temperature decreased from about 26 to 16.2+/-0.4 keV. This is consistent with the previously proposed scenario of increase in mass accretion rate while the inner radius of the magnetically disrupted accretion disc shrinks, thereby lowering the shock temperature. A NuSTAR observation also revealed a high-amplitude WD spin modulation of the very hard X-rays with a single-peaked profile, suggesting an obscuration of the lower accretion pole and an extended shock region on the WD surface. The X-ray spectrum of GK Per measured with the Swift X-Ray Telescope varied on time-scales of days and also showed a gradual increase of the soft X-ray flux below 2 keV, accompanied by a decrease of the hard flux above 2 keV. In the Chandra observation with the High Energy Transmission Gratings, we detected prominent emission lines, especially of Ne, Mg and Si, where the ratios of H-like to He-like transition for each element indicate a much lower temperature than the underlying continuum. We suggest that the X-ray emission in the 0.8-2 keV range originates from the magnetospheric boundary.